2017
DOI: 10.1631/jzus.b1600473
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of human papillomavirus 16/18 genotyping in low-grade cervical lesions preceded by mildly abnormal cytology

Abstract: Histological low-grade squamous intraepithelial lesion/cervical intraepithelial neoplasia grade 1 (LSIL/CIN1) preceded by normal or mildly abnormal cytology is recommended for conservative follow-up, with no separated management. In this study, we assessed the triage value of human papillomavirus (HPV) 16/18 genotyping in 273 patients with LSIL/CIN1. HPV16/18 genotyping was performed at baseline and follow-up was at 6-monthly intervals for up to 2 years. At each follow-up, women positive for cytology or high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Some studies reported that genotyping techniques might be useful to improve the triage and follow up of HPV infected women [17]. In fact, some authors suggested that the genotypes 16/18 are related to a more elevated progressive risk [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that genotyping techniques might be useful to improve the triage and follow up of HPV infected women [17]. In fact, some authors suggested that the genotypes 16/18 are related to a more elevated progressive risk [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The risk for developing low or high-grade cervical lesions originating from cytological abnormalities increases with age 31 ; therefore, HPV detection is recommended in women older than 30 years. However, the average onset of sexual activity in Mexico is at the age of 16 32 , and considering that HPV transformation processes can take 5-10 years, there is a possibility that some young women, under 30 years, may develop premalignant lesions or cancer without falling into the group of women older than 30 in whom HPV detection is recommended.…”
Section: Hr-hpv Dna Detection Tests As Primary Screening For Cervical Cancermentioning
confidence: 99%
“…The main RNA detection techniques for E6 and E7 viral oncogenes include the PreTect® HPV-Proofer and the APTIMA® tests. The PreTect® HPV-Proofer test allows the detection of five types of HR HPV 16,18,31,33,45 with high sensitivity for the detection of high-grade squamous intraepithelial lesions (HSIL); however, it has not been approved by the FDA for use in CC screening 37 .…”
Section: Detection Of E6 and E7 Oncogenes Messenger Rnasmentioning
confidence: 99%
“…Low-grade squamous intraepithelial lesion (LSIL) presents productive viral infection and corresponding clinical measures will be in place. Around 70–80% LSIL are able to regress spontaneously within 1–2 years, but 30% LSIL are refractory and 10% LSIL patients will develop high grade SIL (HSIL) that could evolve into a malignancy [ 5 ]. According to cervical carcinoma screening guideline of NCCN, clinical observations are recommended for treatment of LSIL, accompanied with close follow-up Pap tests and colposcopic examinations until the lesions resolve.…”
Section: Introductionmentioning
confidence: 99%